Psychology of communication approach in islamic studies - Dewi, Trisia Megawati Kusuma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This article aims to explore fear appeal and anxiety in attitude change based on the perspective of Islamic Studies with a psychology of Religion and communication approach. The psychological approach in Islamic studies is one of the approaches widely used to identify human behavior. Methods: This research is a qualitative study with a library research method based on reference searches sourced from several books and journals that can be accessed online through Scopus which are analyzed using bibliometric analysis with VOSviewer. Results: The results of the analysis found that fear appeal and anxiety influence in attitude change can be understood through Islamic Studies.